The History of Hakka Diaspora in Indonesia: Migration Waves and Negotiations with National Identity - Kusuma, Bayu Mitra A.; Octastefani, Theresia (Talenta Publisher, 2022)
The Hakka Diaspora is one of the immigrant descendants who have lived in Indonesia for a very long time. Their existence has often experienced ups and downs. This study aims to analyze the waves of Hakka migration to Indonesia and how they negotiate with national identity. This study used a descriptive qualitative approach to analyze this phenomenon with data collected from interviews and literature studies. The research results showed that the wave of Hakka migration to Indonesia does not only come from mainland China but also from Taiwan. The Hakka migration waves from mainland China largely occurred during the Qing dynasty due to overcrowded populations, the difficulty of land ownership, and government discrimination problems. Meanwhile, the Hakka migration from Taiwan occurred after the Treaty of Shimonoseki in 1895, which forced the Qing dynasty to surrender Formosa to Japan after the First Sino-Japanese war and mass company relocation in the 1980s due to rising production costs in Taiwan. Second, to negotiate their background with Indonesian identity, the Hakka have five philosophies of life called Hakkacita. This philosophy emphasizes conscience, good virtue, cohesiveness, devotion, and shared prosperity between Hakka descendants and other ethnic groups within the framework of Indonesian nationalism.